Improving the thermoelectric solar still performance by using nanofluids– Experimental study, thermodynamic modeling and energy matrices analysis. (October 2021) - Shoeibi, Shahin; Rahbar, Nader; Abedini Esfahlani, Ahad; Kargarsharifabad, Hadi
Highlights: The characteristic equation of the thermoelectric heating and cooling solar still is carried out. The good agreement with proposed model and experiments results. The productivity of solar still with MWCNT, CuO, Al2 O3 and TiO2 nanofluids were increased by 11.57%, 7.16%, 6.32% and 4.66%. The CPL of the thermoelectric solar still with nanofluid is always higher than thermoelectric solar still without nanofluid. Abstract: Numerous studies have been conducted over the past decades to improve the performance of energy systems using nanofluids. This research seeks to evaluate the effect of the simultaneous use of thermoelectric cooling and heating application with various nanofluids on the performance of solar still. The nanofluid temperature decreases with thermoelectric cold side in the cooling tank and flows on the glass by the pump, resulting in reducing the temperature of the glass. Simultaneously, the thermoelectric hot side increases the nanofluid temperature in the heating tank and flows into a helically coiled heat exchanger inside the solar still. The base fluid in cooling and heating tank was replaced by Al2 O3, TiO2, CuO and MWCNT nanofluids at concentrations of 0.1, 0.3, 0.5, 0.7, and 0.9%, and their effect on the temperature difference between saline water and glass were examined. The results showed that water productivity of solar still with the thermoelectric cooling and heating and Al2 O3, TiO2, CuO and MWCNT nanofluids at a concentration of 0.9% were improved by 11.57, 7.16, 6.32, and 4.66%, respectively, compared to solar still without nanofluid. Also, the results showed that the water productivity, thermal efficiency, and CO 2 mitigation of solar still improved with increasing the concentration of the nanoparticles in the base fluid. The presented thermoelectric solar still provided a low cost per liter (CPL) by 0.098 /L/m 2 .